Ancient philosophy: A very short introduction - Annas, Julia (Oxford Oxford university press, 2000)
The tradition of ancient philosophy is a long, rich and varied one, in which the notes of discussion and argument constantly resound. This book introduces ancient debates, engaging us with the ancient developments of their themes. Moving away from the presentation of ancient philosophy as a succession of great thinkers, the book gives readers a sense of the freshness and liveliness of ancient philosophy, and of its wide variety of themes and styles.